Pengaruh Pengetahuan terhadap Kesiapan Siswa dalam Menghadapi Bencana Gempa Bumi di SMA Negeri 1 Wedi Kabupaten Klaten - Al Banna, Fakih Hasan; Dewi, Ratih Puspita (Jurnal Pendidikan Geografi Undiksha, 2025)
Disaster knowledge is critical to preparedness. Apart from knowledge, preparedness is an essential aspect of preparedness. This research aims to analyze students' knowledge of earthquake disasters, students' readiness to face earthquake disasters, and the influence of knowledge on students' readiness to face disasters. This research uses quantitative research with a correlational design. The research population was all SMA N 1 Wedi students, totaling 749. The research sample consisted of 263 students, calculated using the 5% Slovin formula. The sampling technique uses a random sampling technique. Data analysis used normality and homogeneity tests followed by product-moment correlation tests. The results of the research are students' disaster knowledge of 83%, which shows that students' knowledge of disasters is categorized as high, and readiness to face disasters of 97%, which shows that students are ready. Moreover,  the hypothesis test carried out obtained a Sig. 0.00 < 0.05 means a significant influence exists between knowledge and students' readiness to face earthquake disasters.